2018
DOI: 10.2147/cmar.s179219
|View full text |Cite
|
Sign up to set email alerts
|

Treatment features of systemic chemotherapy in young adults with unresectable advanced or recurrent gastric cancer

Abstract: PurposeGastric cancer in young adults (GCYA) is known to have distinct clinicopathological features, including a female predominance and diffuse-type histology. Previous reports have focused on patients who had undergone gastrectomy with curative intent. Information concerning the treatment of unresectable advanced- or recurrent-stage GCYA is lacking. Therefore, we aimed to investigate whether the distinct clinicopathological features of GCYA affect the outcome of systemic chemotherapy.Patients and methodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For general-aged GC patients, the standard treatment regimen is systemic chemotherapy, based on the results of randomized controlled trials [78][79][80]. Although GCYA only accounts for a minority of cases in these RCTs, another study that was focused on young patients found that standard chemotherapy may have similar efficacy for these patients [81]. With favorable general conditions and organ function, GCYA patients experienced less adverse events, which may facilitate intensive therapy [81].…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…For general-aged GC patients, the standard treatment regimen is systemic chemotherapy, based on the results of randomized controlled trials [78][79][80]. Although GCYA only accounts for a minority of cases in these RCTs, another study that was focused on young patients found that standard chemotherapy may have similar efficacy for these patients [81]. With favorable general conditions and organ function, GCYA patients experienced less adverse events, which may facilitate intensive therapy [81].…”
Section: Surgerymentioning
confidence: 99%
“…Although GCYA only accounts for a minority of cases in these RCTs, another study that was focused on young patients found that standard chemotherapy may have similar efficacy for these patients [81]. With favorable general conditions and organ function, GCYA patients experienced less adverse events, which may facilitate intensive therapy [81]. With regard to subsequent treatment outcomes after firstline chemotherapy, data were limited in GCYA patients.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer is the fifth most common malignancy in the world [ 1 , 2 ]. It is considered to be the second most common cause of cancer-related death, with a higher incidence in the elderly [ 3 , 4 ]. In the literature, gastric cancer occurs in subjects over the age of 50, although there is an increase in the relative proportion of gastric cancers in young people compared with adults [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered to be the second most common cause of cancer-related death, with a higher incidence in the elderly [ 3 , 4 ]. In the literature, gastric cancer occurs in subjects over the age of 50, although there is an increase in the relative proportion of gastric cancers in young people compared with adults [ 2 , 4 ]. Data on the clinical, biological and prognostic characteristics of gastric cancer in young patients are still controversial.…”
Section: Introductionmentioning
confidence: 99%